A teacher leadership model validation for in-service teachers - Akkaraputtapong, Panya; Nguyen, Hoa Thi Mai; Ngo, Ha Thanh; Ngo, Nga Thi Hang (Frontiers in Education, 2025)
Teachers as leaders in schools have been widely advocated, as they increasingly act as agents of change in education reforms and directly impact students’ outcomes. Developing teacher leadership is critically important for both students and the school’s development. However, teacher leadership is a complex and context-dependent concept and can result in a lack of common language to guide relevant policies and practices. This study aimed to validate a Western model of teacher leadership and develop a Teacher Leadership Scale (TLS) to capture teachers’ leadership perceptions in a non-Western context. Data were collected via a questionnaire from 538 in-service teachers in an Asian context The EFA results (n = 260) yielded a five-factor scale structure, and the CFA results (n = 278) showed that the first-order model (CFI = 0.967, RMSEA = 0.062, SRMR = 0.044, X2/df=2.080) and second-order model (CFI = 0.959, RMSEA = 0.068, SRMR = 0.050, X2/df=2.287) of the five-factor TLS adequately fit the data. The Cronbach’s alphas indicated strong reliability. The study provides empirical evidence that the TLS is valid for gaging teacher leadership among in-service teachers and suggests implications for using the scale as a guide for reflection and development. It also makes a theoretical contribution by unveiling that teacher leadership perceptions may differ between Western and non-Western contexts.